'People form their own support systems – like forming their own families': the role of parents and friends in the first year at dental school. (29th April 2015) - McMillan, W.
Abstract: Most students experience the transition from school to university as challenging. Students from backgrounds with little or no experience of higher education are most vulnerable in the transition, and most at risk of academic failure or early departure. This study examined the role that parents and friends play in the transition to university and in the first academic year. The study examines the mechanisms of this support so as to understand the ways in which support is provided. It examines whether – and if so, how – support mechanisms differed for first‐generation students and those with family familiarity of university. Data were collected through focus group and individual interviews with dentistry students in their first and second academic years at a Faculty of Dentistry in South Africa. Concepts from psychology literature – attachment and friendship quality – provided the analytical framework. Findings from the study suggest that the social relationships which students have access to during the transition and the first academic year have the potential to provide emotional resources which ease transition and practical information about appropriate ways of being and doing at university. First‐generation university students are less likely to have access to the latter because their parents have no experience of university. The study concludes with suggestions for ways in which universities and their teachers might provide support for all first‐year students.